Modeling Cultural Resilience of the Turonggo Yakso Tradition to Foster Students’ Independence and Cultural Literacy: A Confirmatory Factor Analysis and Structural Equation Modeling Approach - Maria Ulfa Julistiyana; Intan Susetyo Kusumo Wardhani; Yovita Puspasari (Universitas Islam Balitar, 2026)
The study explores the cultural resilience model of Turonggo Yakso as an instrument for strengthening students’ independence and cultural literacy in elementary education. The research aims to verify the validity and reliability of three latent constructs cultural resilience, independence, and cultural literacy and to analyze the structural relationships among them. A quantitative confirmatory design was implemented through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) approach. Data were obtained from 330 elementary school students in Trenggalek Regency, East Java, who participated in learning activities integrated with local art traditions. The analysis employed a five-point Likert scale questionnaire processed with SmartPLS 4.0. Results demonstrated that all constructs met the reliability and validity criteria, indicating strong internal consistency. Cultural resilience exerted a substantial positive influence on both cultural literacy and independence, suggesting that engagement in local culture enhances students’ autonomy and appreciation of cultural values. The coefficient of determination revealed that cultural resilience and cultural literacy explained a considerable proportion of the variance in students’ independence. The overall model fulfilled the acceptable fit criteria, confirming its empirical robustness. Findings indicate that embedding local cultural practices through Turonggo Yakso can promote independent learning and strengthen cultural literacy. The proposed model contributes to the development of culturally responsive pedagogy aligned with the Merdeka Belajar policy and supports the realization of the Profil Pelajar Pancasila.